Leadership of a Company MERCADONA - Adalmiro, Pereira; Angela, Vaz; Clara, Coelho; Cristiana, Sousa; Inês, Rocha (RA Journal of Applied Research, 2022)
The company Mercadona was chosen for this work, as it is an innovative organization marked by its recent internationalization. We carry out the characterization of the company, referring to its mission, vision and values. Next, we will present the organization chart of the company that shows how it is divided in terms of management levels and their respective competencies. Subsequently, we made a brief description of the leader, showing some aspects of his journey to the present and relating these characteristics to the subject under study (social responsibility, corporate governance, etc.) and to his leadership style. Furthermore, we analyze the strategy present at Mercadona, addressing the topics taught in the curricular unit concerning competitive advantage and competitive systems. In short, we intend to conclude about the type of leadership that Juan Roig chooses to obtain adhesion and success in his company.